2020
DOI: 10.21203/rs.3.rs-39676/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nanopolystyrene Translocation and Fetal Deposition After Acute Lung Exposure During Late-Stage Pregnancy

Abstract: Abstract Background: Plastic is everywhere. It is used in food packaging, storage containers, electronics, furniture, clothing, and common single-use disposable items. Microplastic and nanoplastic particulates are formed from bulk fragmentation and disintegration of plastic pollution. Plastic particulates have recently been detected in indoor air and remote atmospheric fallout. Due to their small size, microplastic and nanoplastic particulate in t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 56 publications
2
9
0
Order By: Relevance
“…If negative health consequences persist into the F3 generation, without subsequent exposure, this is considered a transgenerational effect because these offspring have never been exposed to particles or a hostile gestational environmental associated with the original F0 insult [7]. Nano-TiO 2 has been shown to cross the placenta [8] during gestational exposure and potentially deposits into the pup [9], however perturbations in vasoreactivity within the uterus of the dam and/or the placenta of the pup alone are enough to result in detrimental fetal health consequences [10].…”
Section: Introductionmentioning
confidence: 99%
“…If negative health consequences persist into the F3 generation, without subsequent exposure, this is considered a transgenerational effect because these offspring have never been exposed to particles or a hostile gestational environmental associated with the original F0 insult [7]. Nano-TiO 2 has been shown to cross the placenta [8] during gestational exposure and potentially deposits into the pup [9], however perturbations in vasoreactivity within the uterus of the dam and/or the placenta of the pup alone are enough to result in detrimental fetal health consequences [10].…”
Section: Introductionmentioning
confidence: 99%
“…The morphology and particle size of inhaled PM 2.5 or UFPs in the human body are usually characterized by microscopic techniques, including optical and electron microscopies. 14,16,24,25 A variety of optics-based microscopic techniques have been developed in recent years (e.g., confocal laser scanning microscopy (CLSM) 26,27 and enhanced hyperspectral microscopy 28,29 ), making the detection of PM 2.5 in biological tissues much easier. Compared with optical microscopy, electron microscopic (EM) techniques with transmission electron microscopy (TEM) and scanning electron microscopy (SEM) being the most used are more suitable for characterizing PM 2.5 or UFPs because of their simpler pretreatment (e.g., without dyeing), higher magnification, and more powerful qualitative capacities when being equipped with other accessories (e.g., EDX or EELS).…”
Section: Of Pm 25 and The Corresponding Methodologiesmentioning
confidence: 99%
“…Although the significance is still to be determined, maternally inhaled pollutants can translocate to the developing fetus. Studies have demonstrated the deposition of the inhaled pollutants in the placenta (Liu et al, 2021) and other organs within the fetus (Fournier et al, 2020). Recognizing the risk for lifelong health ramifications, efforts should be made to decrease the incidence of premature births associated with prenatal exposure to unhealthy air.…”
Section: Pregnancymentioning
confidence: 99%